2019
DOI: 10.1111/ijcp.13312
|View full text |Cite
|
Sign up to set email alerts
|

Reducing antibiotic prescribing for lower respiratory tract infections 6 years after a multifaceted intervention

Abstract: Summary Aims Few studies have evaluated the long‐term impact of interventions on antibiotic prescription for lower respiratory tract infections (LRTI). This study was aimed at evaluating the use of antibiotics prescribed for LRTIs by general practitioners (GP) who underwent a multifaceted intervention carried out 6 years earlier. Methods General practitioners who had completed two registrations in 2008 and 2009 were again invited to participate in a third audit‐based study in 2015. A multifaceted intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The study also identi ed ve TDF domains that affect patients to demand unnecessary antibiotics, three of which were included in the behavior change strategy: habits, social in uences and lack of intention to change behavior. The study demonstrated the complexity of the in uences that are linked with the behaviors and the importance of developing a multifactorial intervention as identi ed in several studies (34)(35)(36).…”
Section: Discussionmentioning
confidence: 70%
“…The study also identi ed ve TDF domains that affect patients to demand unnecessary antibiotics, three of which were included in the behavior change strategy: habits, social in uences and lack of intention to change behavior. The study demonstrated the complexity of the in uences that are linked with the behaviors and the importance of developing a multifactorial intervention as identi ed in several studies (34)(35)(36).…”
Section: Discussionmentioning
confidence: 70%
“…The study also identi ed ve TDF domains that affect patients to demand unnecessary antibiotics, three of which were included in the behavior change strategy: habits, social in uences and lack of intention to change behavior. The study demonstrated the complexity of the in uences that are linked with the behaviors and the importance of developing a multifactorial intervention as identi ed in several studies (34)(35)(36).…”
Section: Discussionmentioning
confidence: 70%
“…Prescription guidelines have since become standard in Catalan primary care. There have also been periodic public health campaigns and locally successful interventions to reduce prescribing through professional training and discussion (Belomote 2016 ; Molero et al 2019 ). Moreover, all the GP informants commented favorably on a point of care test for the detection of A streptococci bacteria, or “strep-A” test, being made available in Catalonia.…”
Section: Prescribing and Consuming Antibiotics In Cataloniamentioning
confidence: 99%